Thermo-Responsible Sol-Gel Transition of Bioabsorbable Hydrogels Consisting of Enantiomeric A-B-A Tri-Block Copolymers of Poly(lactic acid) (A) and Poly(oxypropylene-co-oxyethylene) (B) - Lee, Chanwoo (Asian Journal of Chemistry, 2014)
For the purpose of controlling gelation rate of the above suspension, the A-B-A triblock copolymers system comprising PLLA-PN-PLLA and PDLA-PN-PDLA was synthesized using PN (Pluronic®) in stead of PEG. Since PN is a non-ionic macromolecular surfactant that can aggregate into micelles in aqueous solution in itself, not only the stereocomplexation of PLLA and PDLA segments but also the phase change behaviour of PN are expected to comtribute to the sol-gel transition of the mixed suspension of enantiomeric copolymers to realize a sharp sol-gel change. Based on the results of these studies, we will discuss the changes in hydrophilic/hydrophobic balance in these copolymers that gives rise to the controlled gelation time and gel strength.